in military and security institutions Women's empowerment (قضايا سياسية, 2023)
The current study seeks to examine the issue of empowering women within the security and military institutions to improve organizational effectiveness and develop the human aspect within these institutions. Empowerment derives its importance because it encourages Iraqi women to participate in this sector. Since 2003, the challenge of terrorism has emerged as the most important obstacle that stood in the way of achieving development plans and moving forward in building a new life and a better future for future Iraqi generations. This entails that women, who are half of society, stand side by side with men, and work in all sectors, to fulfil development plans. As the deterioration of the security situation has affected all aspects of life in Iraq, the presence of women in military and security institutions has become indispensable to benefit from their potential and capabilities, and consolidate the culture of justice to achieve sustainable development and community security. This study’s results and suggestions draw upon the responses to sixty questionnaire distributed to female employees and affiliates within the Iraqi defense and interior ministries.